2015
DOI: 10.1152/japplphysiol.01108.2014
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte response to contraction mode-specific resistance exercise training in human skeletal muscle

Abstract: Skeletal muscle satellite cells (SCs) are important for muscle repair and hypertrophy in response mechanical stimuli. Neuron-glial antigen 2-positive (NG2(+)) and alkaline phosphatase-positive (ALP(+)) pericytes may provide an alternative source of myogenic progenitors and/or secrete paracrine factors to induce Pax7(+) SC proliferation and differentiation. The purpose of this study was to investigate NG2(+) and ALP(+) cell quantity, as well as SC content and activation, in human skeletal muscle following prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 45 publications
4
27
0
Order By: Relevance
“…The relatively infrequent occurrence of MyoDϩ satellite cells can make their quantification problematic but serves to highlight the likely quiescent state of the collective satellite cell pool pre-BR. These data are supported by a recent manuscript showing the limited abundance of activated satellite cells in the basal state (2). Although our MyoD data argue against satellite cell expansion, we cannot discount a potential effect of the functional testing.…”
supporting
confidence: 87%
“…The relatively infrequent occurrence of MyoDϩ satellite cells can make their quantification problematic but serves to highlight the likely quiescent state of the collective satellite cell pool pre-BR. These data are supported by a recent manuscript showing the limited abundance of activated satellite cells in the basal state (2). Although our MyoD data argue against satellite cell expansion, we cannot discount a potential effect of the functional testing.…”
supporting
confidence: 87%
“…Muscle biopsies were obtained before and after the training period from the middle section of the vastus lateralis muscle on the dominant leg, using the Bergstr€ om needle technique (Bergstrom, 1975) and a part of the sample was then treated for immunohistochemistry, as previously described (Farup et al, 2015a). The rest of the sample was immediately frozen in a bath of liquid nitrogen.…”
Section: Muscle Biopsymentioning
confidence: 99%
“…Furthermore skeletal muscle pericytes are also considered to be myogenic precursors distinct from satellite cells, themselves thought to be the primary source of postnatal myoblasts (Zammit et al, 2006). Farup et al reported that native human muscle pericytes respond to contraction mode-specific resistance exercise and notably decline in number (Farup et al, 2015). This correlates with concomitant increases of CD90 + and PDGFRα + mesenchymal stem/stromal and Pax7 + satellite cell pools, suggesting the contribution of pericytes to muscle progenitor pool expansion following prolonged resistance training.…”
Section: Function In Muscle Development and Homeostasismentioning
confidence: 99%